Pendapatan nasional dan pertumbuhan ekonomi: Konsep dasar, kegunaan statistik pendapatan nasional, pertumbuhan ekonomi - Sanihah, Mutia; Kusumawati, Wulan; Ramadhan, Danang Dwiky (Maliki Interdisciplinary Journal, 2024)
The aim of writing this article is to determine the condition of Indonesia’s national income and economic growth in the last 3 years, compare the income earned by Indonesia and Singapore, and determine the usefulness of social income data statistics. The method for writing this article is a qualitative descriptive method, which uses data from literature sources and data from the central statistical agency. Information was obtained that GDP in Singapore reached US 48,595 per person per year, while in Indonesia it was only US 3,452 per person per year and the quality of human resources in Singapore reached 21.02 percent, and this shows that the level of human resource quality in Singapore is higher compared to level of human resource quality in Indonesia. However, economic growth in Indonesia in the last three years has continued to increase, it was recorded that in 2021 the highest economic contribution was the island of Java, the economic contribution given was 57.89 percent. Indonesia’s national income also continues to increase, data obtained in 2021 (tax revenue) was recorded at IDR 6,649,867.3, in the following year it was IDR 8,161,769.6, then in 2023 the total was IDR 8,494,153.7. And national income in non-tax revenues in 2021 amounted to IDR 921,999, in the following year it increased to a total of 1,022,869.8 but in 2023 it decreased to IDR 852,927.6.